Carbohydrate Intake Practices and Determinants of Food Choices During Training in Recreational, Amateur, and Professional Endurance Athletes: A Survey Analysis - Reinhard, Corinne; Galloway, Stuart D. R. (Frontiers in Nutrition, 2022)
Carbohydrate (CHO) intake during exercise can optimize endurance performance. However, there is limited information regarding fueling practices of endurance athletes during training. Accordingly, an anonymous German-language online survey was circulated examining the determinants of CHO choices, and intake practices among runners, triathletes, and cyclists during training. Survey questions included predefined answers, and a Likert scale with response of CHO food choice intakes from 1=never to 5=always. 1081 endurance athletes (58.0% male, 68.6% aged 18-39 years) of varying competitive levels were included in the analysis. Overall, most athletes consumed a combination of commercial sport nutrition products and everyday foods (67.4%, n=729) with their primary reason that food-first was preferred, but in some exercise scenarios, commercial sport nutrition products were deemed more convenient (61.3%, n=447). Athletes consuming commercial sport nutrition products only (19.3%, n=209) most often valued their ease of intake during exercise (85.2%, n=178). Among those consuming everyday foods only (13.2%, n=143), the most common reason was the perceived importance of eating wholesome foods/natural ingredients (84.6%, n=121). Between the most frequently consumed CHO sources during training at low-to-moderate intensities (n=1032), sports drinks (mean±SD; 2.56±1.33) were consumed significantly more often than bananas (2.27±1.14, p<0.001), with no significant difference in intake frequency between bananas and traditional muesli/fruit/energy bars (2.25±1.14, p=0.616). Whereas during high intensities (n=1077), sports drinks (3.31±1.51) were significantly more often consumed than gels (2.79±1.37), and gels significantly more often than energy bars (2.43±1.28), all commercial sport nutrition products (all, p<0.001). Overall, 95.1% (n=1028) of all athletes consumed CHO during training at all exercise intensities, with males (n=602; 2.35±0.70) consuming significantly more often commercial sport nutrition products than females (n=424; 2.14±0.79, p<0.001); females consumed significantly more often everyday foods than males (1.66±0.47 vs. 1.54±0.42, p<0.001). Most athletes used mixed CHO forms during low-to-moderate (87.9%), and high exercise intensities (94.7%). 67.6% (n=731) of all athletes reported guiding their CHO intake rates during training by gut feeling. These large-scale survey findings suggest a preference of endurance athletes’ CHO intake during training in liquid form independent of exercise intensities and offer novel insights into CHO intake practices to guide sports nutrition strategies and education.